Environmental Awareness as a Predictor of English Teachers’ Professional Identity: A Correlational Study - Friscilla Sembiring (Pustaka Karya Mandiri, 2026)
Environmental awareness has become increasingly relevant to teachers’ professional roles because education is expected to contribute not only to academic achievement but also to sustainability-oriented values, responsible citizenship, and meaningful social transformation. For English teachers, environmental awareness may influence how they interpret their role as educators, integrate global issues into language learning, and develop a stronger sense of professional responsibility. This study investigated the relationship between environmental awareness and English teachers’ professional identity. The study employed a quantitative correlational design involving 40 English teachers. Two instruments were used: a 20-item Environmental Awareness Scale and a 20-item Professional Identity Scale. Both instruments used a five-point Likert scale, with total scores ranging from 20 to 100. The data were analyzed using descriptive statistics, level categorization, Pearson product-moment correlation, and simple linear regression. The findings showed that English teachers had a high level of environmental awareness, with a mean score of 82.60 and a standard deviation of 6.36. Their professional identity was also high, with a mean score of 84.93 and a standard deviation of 6.09. The correlation analysis revealed a very strong, positive, and statistically significant relationship between environmental awareness and professional identity, r = .997, p < .001. The regression analysis showed that environmental awareness significantly predicted professional identity, R² = .995, F (1, 38) = 7198.14, p < .001. The regression equation indicated that every one-point increase in environmental awareness was associated with a .96-point increase in professional identity. The study concludes that English teachers who demonstrate stronger environmental awareness tend to report stronger professional identity. These findings suggest that sustainability-oriented awareness may become an important dimension in strengthening English teachers’ professional meaning, responsibility, reflective practice, and instructional commitment.